Foliations with all non-closed leaves on non-compact surfaces - Polulyakh, E. A.; Maksymenko, S. (Methods of Functional Analysis and Topology, 2016)
Let X be a connected non-compact 2-dimensional manifold possibly with boundary and Δ be a foliation on X such that each leaf ωΔ is homeomorphic to R and has a trivially foliated neighborhood. Such foliations on the plane were studied by W. Kaplan who also gave their topological classification. He proved that the plane splits into a family of open strips foliated by parallel lines and glued along some boundary intervals. However W. Kaplan’s construction depends on a choice of those intervals, and a foliation is described in a non-unique way. We propose a canonical cutting by open strips which gives a uniqueness of classifying invariant. We also describe topological types of closures of those strips under additional assumptions on Δ.